The European Union and Iraq: Being concerned demands involvement - Volker Perthes (Stiftung Wissenschaft und Politik (SWP), 2004)
Since the end of June 2004, the Iraqi Interim Government has been trying to use the sovereign powers restored to it to rebuild a credible state. It has three main priorities: first and foremost, security needs to be restored. This has become by far the most important concern to Iraqis, which makes the ostentatious rebuilding of elements of a 'strong state' so popular. Secondly, the interim government seeks to reassure the population that a proper political process is underway. For this reason, the government has been eager to call for a timely national conference which incorporates a broad spectrum of Iraqi groups and coalitions - it is now likely to convene in mid-August. At the same time, and thirdly, the new government has been actively approaching neighbouring countries to persuade them that continued instability in Iraq will harm their interests as well. These initiatives are laudable in essence, yet success is by no means guaranteed. Not least, it is up to the EU and its member states to determine whether, and if so, how, they are willing to support Iraq on its road to independence. (SWP Comments / SWP)
Keywords: 320